Development of Cost Structure Standard Policy - mahfudin mahfudin (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2023)
Official travel activities are the main element in internal audit activities. Currently, variations in the composition of official travel costs for internal audit activities in similar areas are very diverse. The aim of this study is to provide an overview of the policy for standardizing the composition of official travel expenditure in internal audits with similar object coverage. The research method used is a descriptive statistics method. The value of internal audit SSB recommended from this research results for the composition of internal audit official travel is 80% (offline method) and 60% (hybrid method) of the output budget. This figure is intended as the percentage of official travel that is sufficient (effective and efficient) based on the results of the internal audit output benchmarking.